CeCl3·7H2O-NaI-SiO2 Catalyzed Aza-Michael Addition of N-Heterocycles to Enones under Solvent Free Conditions - Young Choi Lee; 이규철; Hyo Won Lee (Bulletin of the Korean Chemical Society, 2012)
KCI Citation Count: 0